Physiological and Anatomical Study of Caraway (Carumcarvi L.) Plant Sprayed with Serine and Arginine - Amal Ghanim Al-Kazzaz (Journal of Global Pharma Technology, 2018)
The study aimed to estimate the effects of two amino acids serine and arginine on Caraway (Carumcarvi L.) plant in the old green garden of College of Education for Pure Sciences Ibn AL-Haitham, Baghdad University, during the growing season 2016-2017. Complete randomized design (CRD) was used to conduct the experiment at two treatment (15, 30) mg.L-1 for serine and two treatment (20 and 40) mg.L-1 for arginine foliar spraying with three replicates, and control treatment sprayed with distilled water. Vegetative growth parameters of plants were estimated (plant height, dry weight, fertilizer relative efficiency and absolute rate growth), chemical contents as (content of nitrogen, phosphorus and potassium, protein and arginine concentration, and total chlorophyll) were determined, and seeds yield per plant were calculated. Results showed the response of growth parameters increased with the foliar spraying of both amino acids treatment as compared to control and highest interaction between the two factors was found between 30 mg.L-1 serine and 40 mg.L-1 arginine. As the anatomical feature the study appears that the foliar spray by amino acids (arginine and serine) and their interaction between Arginine 20 mg.L-1 and Serine 15 mg.L-1, led to increase of the epidermis thickness of stem and diameter of stem, also the amino acid led to increase the cortex thickness of stem about 80.2 µm and thickness of sclerenchyma layers significantly about 54.5 µm comparison with control treatment 40.7µm when treatment the plant with Arginine 20 mg.L-1 and Serine 30 mg.L-1, so the treatment led to decrease the vascular bundles thickness from the control treatment especially the treatment, consist from mixed with 40 mg.L-1 Arginine and 30 mg.L-1 Serine about 42.7 µm from the control treatment 109.1 µm.Key words: Caraway plant, Physiology, Anatomy, Serine, Arginine.